Hydrodynamic Forcing Mobilizes Cu in Low-Permeability Estuarine Sediments - Xie, Minwei; Wang, Ning; Gaillard, Jean-François; Packman, Aaron I (Environmental science & technology, 2016)
Overlying hydrodynamics play critical roles in controlling surface-porewater exchanges in permeable sediments, but these effects have rarely been characterized in low-permeability sediments. We conducted a series of laboratory experiments to evaluate the effects of varied hydrodynamic conditions on the efflux of metals from low-permeability estuarine sediments. Two Cu-contaminated sediments obtained from the Piscataqua River were subject to controlled levels of hydrodynamic shear in Gust mesocosms, including episodic sediment resuspension. Overlying water and porewater samples were collected over the course of experiments and analyzed for metal concentrations. The two sediments had similar permeability (∼10–15 m2), but different particle size distributions. Hydrodynamic forcing enhanced the mobilization and efflux of Cu from the coarser-grained sediments, but not the finer-grained sediments. Sediment resuspension caused additional transitory perturbations in Cu concentrations in the water column. Particulate metal concentrations increased significantly during resuspension, but then rapidly decreased to preresuspension levels following cessation of sediment transport. Overall, these results show that the mobility and efflux of metals are likely to be influenced by overlying hydrodynamics even in low-permeability sediments, and these effects are mediated by sediment heterogeneity and resuspension.